Ahon the Pamintuan Protected Landscape Visitor Center - Tamayao, Rovalie P. (College of Architecture, University of the Philippines Diliman, 2019)
Tourism has been one of the significant economic contributors in the Philippines but it is noticeable that a visitor center is uncommon; instead, what we have are scattered establishments that cater for each small portion of a tourist's need. A visitor center is designed to encapsulate the most essential solutions offered by different building types using Philip L. Pearce's Four Plus Model. This project challenges the conventional building types to combine functions and link spaces of different requirements through effective space planning.